Impact of electronic prescribing on patient safety in hospitals: Implications for the UK - Ahmed,Z; Garfield,S; Jani,Y; Jheeta,S; Franklin,BD (Clinical Pharmacist, 2016)
NHS hospitals in England are expected to be paperless by 2020 as set out in a comprehensive framework published by the National Information Board. The use of hospital electronic prescribing (EP) systems is therefore likely to increase rapidly in the near future. The aim of this review is to summarise the available evidence of the impact of inpatient EP on patient safety, with a focus on implications for the UK. MEDLINE and EMBASE were searched to identify systematic and narrative reviews published between 2000 and 2015 that examined the effects of EP on safety-related outcome measures. A total of ten reviews were identified. The evidence for the effects of EP on medication errors, adverse drug events, workflow, and healthcare professional communication are discussed, as are the potential unintended consequences and how they can be identified and mitigated. The review concludes with considerations of the evolution of EP in healthcare, especially in relation to advances in health information technology, inpatient involvement with their medication in the context of EP, and how EP may be used by policymakers and end users to further benefit patient safety.